Evaluacion de diferentes concentraciones de trichoderma para el control de lancha (phytoptora infestans) en el cultivo de papa (solanum tuberosum) variedad yema de huevo, parroquia Aloag, cantón Mejía, 2023. - Chiguano Pérez, Ángel Marcelo (2024)
The present investigation had as purpose to evaluate three different concentrations of Trichoderma for the control of lancha (Phytopyora infestans) in the potato crop (Solanum tuberosum) in the egg yolk variety in the Alóag parish, province of Pichincha. The research method used was experimental, using a completely randomized design (CRD), which analyzed 4 treatments with 3 replications, using the Infostat program with the Tukey reliability test at 0.05%. The statistical analysis of the obtained data was carried out in the four weeks 15, 30, 45 and 60 days, the main factor was composed by three concentrations: of Trichoderma , the result of the evaluation of the agronomic response for each concentration of Trichoderma revealed significant differences in its capacity to mitigate the effects of the lancha, the investigation allowed to determine the optimal concentration of Trichoderma presenting the concentration in the treatment 2 ( T2) as the most optimal for effective control of the lancha because it presented the lowest incidence of lancha with only 7, 23 % of infected plants, while the optimal concentration as for the development of the crop was the concentration in the treatment 1 (T1), presenting the best averages of germination (25,50%), height of plant (22 cm) and number of leaves (27,15), in the potato crop of the egg yolk variety, presenting better control results and improving plant growth. This analysis carried out in the research has a lot of importance in the field of phytosanitary control in the potato production sector. It is recommended to continue to carry out additional research to refine and adjust the concentrations of Trichoderma used. This will allow to determine with greater precision the most effective concentration for the control of the spear, considering factors such as environmental variability and the specific conditions of the crop.